2019
DOI: 10.1101/652396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polygenic risk score of alcohol consumption predicts alcohol-related morbidity and all-cause mortality

Abstract: ObjectiveTo develop a highly polygenic risk score (PRS) for alcohol consumption and study whether it predicts alcohol-related morbidity and all-cause mortality.DesignBiobank-based prospective cohort studySettingFinnGen Study (Finland)Participants96,499 genotyped participants from the nationwide prospective FinnGen study and 36,499 participants from prospective cohorts (Health 2000, FINRISK, Twin Cohort) with detailed baseline data and up to 25 years of follow-up time.Main outcome measuresIncident alcohol-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Rehm and colleagues (2013) even suggested that heavy alcohol use over time could be used as a definition of alcohol use disorder, which also implies no sharp distinction between alcohol use disorder and other heavy drinkers. Correspondingly, genetic factors affect the risk of heavy alcohol use, alcohol use disorder, and alcohol dependence (Liu et al, 2019;Sanchez-Roige et al, 2018) but as a continuum, in a relatively linear fashion (Kiiskinen et al, 2019).…”
Section: The Population Mean Predicts the Number Of Deviant Individualsmentioning
confidence: 99%
“…Rehm and colleagues (2013) even suggested that heavy alcohol use over time could be used as a definition of alcohol use disorder, which also implies no sharp distinction between alcohol use disorder and other heavy drinkers. Correspondingly, genetic factors affect the risk of heavy alcohol use, alcohol use disorder, and alcohol dependence (Liu et al, 2019;Sanchez-Roige et al, 2018) but as a continuum, in a relatively linear fashion (Kiiskinen et al, 2019).…”
Section: The Population Mean Predicts the Number Of Deviant Individualsmentioning
confidence: 99%